Tradisi Pembacaan Maulid Barzanji Dalam Perspektif Fenomenologi-Dekonstruksi Derrida - Mukarom, Ahmad Soheh; Furqon, Syihabul; Busro, Busro (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This paper examines the text of Maulid Al-Barzanji. The sacred text contains the personality of the Prophet Muhammad, which implies one side of the myth of the Prophet, as an idol through the text and what the implications are when the text is deconstructed. The writing uses Derrida's phenomenological approach through deconstruction operations to uncover the camouflage aspects of the text on the one hand and the field of sacredness on the other. Meanwhile, Derrida's theory of deconstruction will operate sequentially looking for the roots where religion has become mere rites and myths. Because, it is clear that the root of religious myth is the text, in addition to the crystallization of idols. Research shows that in the text of Maulid al-Barzanji found fields of the sacredness of the text, about how the text preaches the divine side of the Prophet, as well as its significance as an ordinary human being (basyar). In addition, it was found that in the barzanji tradition, there was no crystallization of the Prophet's idol.Tulisan ini mengkaji teks Maulid Al-Barzanji. Teks sakral tersebut berisi personalitas Nabi Muhammad SAW yang mengimplikasikan satu sisi pemitosan Nabi Muhammad SAW sebagai idol melalui teks dan bagaimana implikasinya ketika teks didekonstruksi. Tulisan ini menggunakan pendekatan fenomenologi Derrida melalui operasi dekonstruksi untuk membongkar aspek kamuflatif teks di satu sisi dan medan sakralitas di sisi lainnya. Sementara teori dekonstruksi Derrida akan beroperasi secara sekuensial mencari akar-akar di mana agama telah jadi sekadar ritus dan mitos. Sebab, jelas bahwa akar dari pemitosan agama adalah teks, di samping pengkristalan idol. Penelitian menunjukan bahwa dalam teks Maulid al-Barzanji ditemukan medan-medan sakralitas teks, ihwal bagaimana teks mengabarkan sisi Ilahiah Nabi SAW, sekaligus signifikansinya sebagai insan biasa (basyar). Di samping itu ditemukan fakta bahwa dalam tradisi barzanji, tidak terjadi pengkristalan idol Nabi.